IRP OBLIGATION FOR THE FORMALIZATION OF INDEPENDENT PROFESSIONALS - Antonio Jara Duarte, Cesar; Javier López Núñez, Hugo (Revista Gênero e Interdisciplinaridade, 2023)
This research work aims to demonstrate whether taxpayers comply with the tax formalities in this specific case the personal income tax of independent professionals, since it is important to know this data to improve the formality in our country therefore seek solutions to these problems. Our quantitative approach gave us statistical data with more accurate results, a descriptive investigation was planned, through closed surveys to find out exactly what the real situation is in the formal sphere, resulting in a majority being unaware and in other cases omitting to avoid contributing to state coffers due to disagreement with the management of state economic resources. It is important to note that the majority of the taxpayers of this tax obligation are not satisfied with what is established by the State, so it helps or a factor is created to try to find other alternatives to be informal and therefore avoid contributing or paying less than the established taxes.